Political news on Instagram: influencer versus traditional magazine and the role of their expertise in consumers’ credibility perceptions and news engagement - Zimmermann, Daniel; Klee, Asina; Kaspar, Kai (Frontiers in Psychology, 2023)
Introduction Social networking sites (SNS) are increasingly used by consumers to read and share political news. In this context, Instagram plays an important role due to its prevalence and visual characteristics. However, previous research has highlighted that consumers fail to identify the source of online news, though source characteristics were shown to be vital for news credibility perceptions. Nevertheless, research on whether and which source characteristics have an influence on Instagram consumers’ credibility perceptions and news engagement intentions are lacking. The present study addresses this empirical gap by investigating potential effects of source expertise and source type on source credibility, message credibility, news engagement intentions, and personal involvement regarding political news on Instagram. Method We randomly presented participants with political news posts from one of four sources, either the Instagram representation of a fictional news magazine or influencer with or without political expertise. Participants assessed the perceived credibility of the source and the news, their news engagement intentions, and personal involvement. Results We analyzed data from 416 participants. Results showed significant main effects of source expertise on each of the dependent variables. Those were shown to be indirect effects through personal involvement. There were hardly any effects of source type. Discussion These results provide new insights into the role of source expertise on credibility perceptions and news engagement intentions, and provide insights into the comparison between influencers and Instagram representations of traditional news magazines. Theoretical implications for future research and practical implications for content creators, users, and SNS platforms are discussed.